(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to find out organizational and inter-organizational behavior, lower-level bureaucratic behavior, and target group behavior in implementing the Manggala abattoir revitalization program (RPH) in Makassar City. This study used a qualitative research method with a descriptive type. The number of informants in this study were 8 people. Data collection techniques were observation, interview, and documentation methods. The results of the study indicated 3 (three) implementations of the Manggala slaughterhouse revitalization program policy in Makassar City, namely: 1) Organizational and inter-organizational behavior with two variables, namely commitment and coordination, which had been implemented well, 2) Bureaucratic behavior. the lower level with the discretionary dimension of the Department of Fisheries and Agriculture and 12 RPH officers had collaborated to socialize or convey to beef meat entrepreneurs about how to slaughter large livestock at the Manggala RPH based on the applicable standard operating procedures (SOP), and 3) Target groups from The implementation of the RPH revitalization program policy had been right on target, but there were still many beef meat entrepreneurs who had not joined the RPH because they had private RPH so that the government had not acted to direct all animals slaughter to be carried out at the government-owned RPH. Keywords: Policy Implementation, RPH Revitalization Program